2015
DOI: 10.1097/aud.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Tinnitus As an Independent Correlate of Tinnitus Severity

Abstract: Findings add to the growing body of work, supporting the unique and important role of acceptance in tinnitus severity. The utility of the concept is discussed in relation to the development of new psychological models and interventions for tinnitus severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…One of the survey respondents who rated tinnitus as “not a problem” also commented: “the…[TCQ] questionnaire I found quite difficult as I just don’t think about these things, I felt that my responses might come over as negative when actually I just do not have these thoughts about tinnitus at all.” Similar conclusions have been drawn from research into the concept of tinnitus acceptance, which can be defined as “an open, mindful and nonevaluative approach to internal experiences” (Hesser et al 2012, p. 650). In questionnaire studies, both Hesser et al (2015) and Riedl et al (2015) found tinnitus acceptance to be negatively correlated with tinnitus distress. In other words, people who were not very distressed by their tinnitus tended not to become engaged in thinking about it.…”
Section: Discussionmentioning
confidence: 98%
“…One of the survey respondents who rated tinnitus as “not a problem” also commented: “the…[TCQ] questionnaire I found quite difficult as I just don’t think about these things, I felt that my responses might come over as negative when actually I just do not have these thoughts about tinnitus at all.” Similar conclusions have been drawn from research into the concept of tinnitus acceptance, which can be defined as “an open, mindful and nonevaluative approach to internal experiences” (Hesser et al 2012, p. 650). In questionnaire studies, both Hesser et al (2015) and Riedl et al (2015) found tinnitus acceptance to be negatively correlated with tinnitus distress. In other words, people who were not very distressed by their tinnitus tended not to become engaged in thinking about it.…”
Section: Discussionmentioning
confidence: 98%
“…In other words, we need to identify factors that may contribute to the relationship between anxiety and tinnitus, such as latent traits or states that may help explain this relationship. It is also important to consider an individual's response to the daily experience of tinnitus since coping strategies, such as acceptance, have been found to be more adaptive for people living with chronic tinnitus (Hesser et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Sullivan and colleagues [23] also reported that those with depression associated with tinnitus used less problemsolving active coping strategies than those who were not depressed. On the other hand, habituation and tinnitus acceptance has been found to relate to lower tinnitus distress, reduced anxiety and depression and better long-term outcomes [56,57].…”
Section: Coping Stylesmentioning
confidence: 99%